IMPLEMENATION OF INDEPENDENT LEARNING IN CIVIL ENGINEERING STUDENTS IN APPLIED PHYSICS COURSE - Stefany Margareta Martono; Vina N Van Harling (SOSCIED, 2023)
This Applied Physics course applies independent learning in learning activities in the classroom. The application of independent learning in this course is an effort to increase learning activities in class so that students can more easily participate in class learning. The method used in this study is a qualitative description method. Researchers collected data in the form of notes on the learning process and questionnaires at the end of the lesson and the final grades of the semester. The learning process data was taken on average from 32 students who had attended at least 12 face-to-face meetings in class. The average data that has been calculated is that during the learning process 67% of students are able to participate in learning activities with a score of 79 and 80. At a score of 81 – 100, there are 33% of students who are very able to participate in the learning process. The results of the written test data averaged 22 students with a percentage of about 69% of students who were quite capable in learning Applied Physics. As many as 3 students with a percentage of 9% needed guidance in learning Applied Physics. As many as 6 students with a percentage of 19% are capable in learning Applied Physics. There is 1 student with a percentage of 3% who is very capable in learning Applied Physics. Questionnaire data as supporting data that assesses the teaching process carried out by teaching lecturers, it can be seen that the average final score is 4.53 which is filled in by 47 students. Based on the data that has been analyzed, it can be concluded that the application of independent learning in Applied Physics courses can be applied but requires further efforts to improve in developing materials and adjusting technological developments